UNRAVELING THE THREADS OF WOMANHOOD: A QUALITATIVE INQUIRY INTO THE CONSTRUCTION OF GENDER IN SASAK SOCIETY - Ilhami, Hablun; Rohmaniyah, Inayah (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2023)
Sasak society is renowned for its adherence to moral principles, humanism, and strong religious beliefs. Nevertheless, several research indicate the persistent existence of gender discrimination, particularly targeting women. This study seeks to examine the formation of the concept of 'being a woman' in Sasak culture, encompassing its many manifestations, underlying causes, and consequences for the social framework, particularly for women in Sasak society. This study employed a qualitative methodology, gathering primary data from several sources including regional chairman, religious leaders, Penelando customary authorities in Sasak, women fulfilling the role of housewives, and males serving as heads of households. The data collected from these sources utilizing the interview method is subsequently analyzed using Foucault's framework of power relations. The research reveals that in Sasak society, the construction of 'being a woman' entails the perception that domestic work is inherent to women. The formation of 'womanhood' in Sasak society is intricately linked to the ideology of male hegemony over women. This architecture significantly influences the occurrence of social issues, including the dual burden faced by women, the marginalization of women in the public domain, and the restricted availability of economic resources for women. Due to the intricate nature of power in the creation of gender, it is imperative to do more research with a broader pool of participants. This will enable the identification of more comprehensive concerns and the exploration of the dynamics within current power dynamics.Masyarakat Sasak selama ini dikenal sebagai masyarakat yang menjunjung tinggi nilai-nilai moral, humanis dan religiusitas yang tinggi. Namun demikian, beberapa penelitian menunjukkan bahwa pada sisi lain masih terdapat fenomena diskriminasi gender, khususnya pada perempuan. Tulisan ini bertujuan untuk mengeksplorasi konstruksi 'menjadi perempuan' di masyarakat Sasak yang meliputi bentuk, faktor penyebab hingga implikasinya pada struktur sosial khususya perempuan di masyarakat Sasak. Penelitian ini dilakukan melalui pendekatan kualitatif, dengan sumber data primer penelitian yang mencakup ketua wilayah, tokoh agama sekaligus ketua adat Penelando di Sasak, perempuan sebagai ibu rumah tangga, serta laki-laki selaku kepala keluarga. Data yang diperoleh melalui metode wawancara dari sumber data tersebut kemudian diinterpretasi dengan menggunakan pendekatan relasi kuasa Foucault. Hasil analisis menunjukkan bahwa bentuk konstruksi 'menjadi perempuan' di masyarakat Sasak adalah bahwa pekerjaan domestik dianggap sebagai kodrat perempuan. Konstruksi 'menjadi perempuan' di masyarakat Sasak ini berkaitan erat dengan wacana dominasi laki-laki terhadap perempuan. Konstruksi tersebut berdampak pada munculnya problem-problem sosial seperti adanya beban ganda perempuan, marginalisasi perempuan di ruang publik, hingga keterbatasan akses sumber ekonomi bagi perempuan. Mengingat sifat kekuasan dalam konstruksi gender yang sangat kompleks, maka perlu adanya penelitian lanjutan dengan informan yang lebih luas, guna mengidentifikasi persoalan-persoalan yang lebih komprehensif serta mengungkap dinamika relasi power yang ada.